B/N-doped carbon sheets from a new ionic liquid with excellent sorption properties for methylene blue - Mehler, Julian; Ermer, Matthias; Paap, Ulrike; Heller, Bettina; Maier, Florian; Steinrück, Hans-Peter; Hartmann, Martin; Korte, Carsten; Schulz, Peter; Wasserscheid, Peter (Journal of Ionic Liquids, 2021)
The pyrolytic treatment of the novel ionic liquid 1-ethyl-3-methyl-imidazolium tetrakis-(1-imidazolyl)borate ([EMIM][BIm4]) allowed the preparation of B/N-doped carbonaceous materials with an exceptional performance in the adsorptive removal of the cationic dye methylene blue (MB) from wastewater. [EMIM][BIm4] was prepared via an easy and scalable synthesis protocol in very good yield. The carbon materials obtained after salt templated pyrolysis of the IL displayed high degrees of heteroatom doping (up to 22 wt% N, 3 wt% B) and high surface areas of up to 1860 m2 g−1. The materials were tested for their performance in the adsorptive removal of MB from contaminated water. Adsorption equilibrium experiments revealed an adsorption capacity exceeding 500 mg g−1, which is, to the best of our knowledge, the highest value reported so far. Time-resolved adsorption experiments showed that the materials not only exhibit high capacity but also very fast adsorption kinetics. Complete decolorization of MB solutions in only 5 min at high MB concentrations of 100 mg L−1 was observed. These results demonstrate that [EMIM][BIm4] is an excellent precursor for the preparation of IL-derived B/N-doped carbon sorbents.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Adsorption; B/N doped carbon nanosheets; Ionic liquid precursor; Material synthesis